Pengaruh Dental Health Education Cara Menyikat Gigi disertai Demonstrasi terhadap Tingkat Pengetahuan Kebersihan Gigi pada Siswa Kelas V SDN Padangdangan 1 - Zakiyah Yasin (Fakultas Kedokteran Gigi Universitas Jember, 2021)
Dental and oral disease are still become health problem in Indonesia. Dental and oral diseases greatly affect the degree of health, growth process and even the future of children. Data about dental diseases on Indonesian children, indicates that condition is already at worried stage. Research of effective health education about dental hygiene to toddler children needed. This study aim is to determine the influence of DHE against knowledge of dental hygiene on Grade V students in SDN Padangdangan 1. The method of this study was quasi experiment, use Pretest- Postest Control design. This study was conducted in SDN Padandangan 1 with total population was all of Grade V students in SDN Padandangan 1. The sampling technique in this study was total sampling with number of respondents was 32 divided by two groups, there were control group and implementation group. The data collected by using questionnaires. The result of this study shows that before DHE applicated to implementation group, students have less knowledge, that was 9 students (56,2%) and after DHE applicated, value of students’ knowledge was increase, that was 16 students (50,0%). The result of Willcoxon Sign Rank Test detired P = 0,005 (p<α), administering DHE through good and correct teeth rushing demonstration to Grade V students can increase the value of students’ knowledge. Dental health education is the right way to brush your teeth by using an interesting tool, such as phantom mannequin that can make attention from educator. Direct practice echnique is also involves many senses so the material from educator was more touches long erm memory.